2015
DOI: 10.1108/jpbm-11-2014-0749
|View full text |Cite
|
Sign up to set email alerts
|

The Nobel Prize: the identity of a corporate heritage brand

Abstract: Purpose – The purpose of this study is to understand the identity of the Nobel Prize as a corporate heritage brand and its management challenges. Design/methodology/approach – An in-depth case study analysed within a heritage brand model and a corporate brand identity framework. Findings – The Nobel Prize is a corporate heritage brand – one whose value proposition is based on heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“… Australia (Byrom and Lehman 2009;Cooper et al 2015a);  China (Balmer and Chen 2015;Schroeder et al 2015);  France (Bargenda 2015);  Finland (Blombäck and Brunninge, 2009;Hakala et al 2011;Hakala et al 2015);  Germany (Wiedmann et al 2011a(Wiedmann et al , 2011b;  Italy (Rindell et al 2015);  New Zealand (Cooper et al 2015a);  Norway (Urde and Greyser, 2015);  Portugal (Rindell et al 2015);  Sweden Brunninge, 2009, 2013;Blombäck and Scandelius 2013;Urde and Greyser, 2015);  United Kingdom (Balmer 2008(Balmer , 2009(Balmer , 2011aBalmer 2014a, 2015);  US (Hudson 2011; Balmer and Hudson 2013).…”
Section: Geographic Scopementioning
confidence: 99%
See 2 more Smart Citations
“… Australia (Byrom and Lehman 2009;Cooper et al 2015a);  China (Balmer and Chen 2015;Schroeder et al 2015);  France (Bargenda 2015);  Finland (Blombäck and Brunninge, 2009;Hakala et al 2011;Hakala et al 2015);  Germany (Wiedmann et al 2011a(Wiedmann et al , 2011b;  Italy (Rindell et al 2015);  New Zealand (Cooper et al 2015a);  Norway (Urde and Greyser, 2015);  Portugal (Rindell et al 2015);  Sweden Brunninge, 2009, 2013;Blombäck and Scandelius 2013;Urde and Greyser, 2015);  United Kingdom (Balmer 2008(Balmer , 2009(Balmer , 2011aBalmer 2014a, 2015);  US (Hudson 2011; Balmer and Hudson 2013).…”
Section: Geographic Scopementioning
confidence: 99%
“…Empirical studies have researched the phenomenon of corporate heritage as a global issue (e.g., Urde et al 2007;Balmer 2009Balmer , 2011bMicelotta and Raynard 2011;Cooper et al 2015b;Urde and Greyser, 2015) and in diverse geographical settings including:…”
Section: Geographic Scopementioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of the corporate communication literature, this philosophy is defined as a sustainable corporate story that describes the what, why, and how of a firm to internal and external stakeholders, as an explanation of the organizational raison d'être (Van Riel, 1997: 302). Core values of organizations reflect on their identity and corporate communication tools (Balmer & Chen, 2015;Balmer, 2011bBalmer, , 2013Urde et al, 2015). The investigation ofİşbank's corporate communication activities demonstrates that certain values associated with the bank's identity that we called corresponding elements, have been expressed constantly since its foundation.…”
Section: Timeless Core Valuesmentioning
confidence: 99%
“…Further studies investigated long-standing organizations, validated prior studies and showed that heritage brands not only focus on marketing communication, which serves to increase sales of products and services by attracting customers, but also focus on communicating with all their stakeholders (Hudson, 2011;Wiedmann et al, 2011;Balmer & Chen, 2015;Urde & Greyser, 2015). Corporate communication, which includes advertising, marketing communications, public affairs, community relations, and employee communications, encompasses all of a company's communication with its internal and external stakeholders, such as customers, investors, media, employees, board members, group leaders, and the general public (Hallahan et al, 2007: 17;Doorley & Garcia, 2007: xii;Wilcox et al, 2015: 36).…”
Section: Introductionmentioning
confidence: 99%